Atomic‐Level Metal Electrodeposition: Synthetic Strategies, Applications, and Catalytic Mechanism in Electrochemical Energy Conversion. Issue 3 (2nd January 2022) - Shi, Yi; Lee, Carmen; Tan, Xianyi; Yang, Lan; Zhu, Qiang; Loh, Xianjun; Xu, Jianwei; Yan, Qingyu
Abstract : Electrochemical energy conversion is considered a promising method to alleviate the global energy crisis and environmental issues. By decreasing the length scale to the atomic level, the energy‐related metal electrocatalysts can possess unique catalytic properties, which can maximize their utilization. The electrodeposition technique has gained unprecedented attention for the synthesis of atomic‐level metal catalysts. In this review, the recent progress on the various strategies used to electrodeposit atomic‐level metal catalysts is summarized. The basic principles of the surface‐limited electrochemical techniques (underpotential deposition (UPD)) and their applications in the self‐terminating growth of atomic‐level metal catalysts are highlighted. This review also discusses the mechanistic investigations, comprehensive understanding of the structure–activity relationships at the atomic level and the application of these atomic‐level catalysts in the electrochemical energy conversion in details. Finally, the current challenges and future directions on the potential use of the atomic level electrodeposition are presented. Abstract : The advances in atomic‐level metal electrodeposition for electrochemical energy conversion are systematically summarized and discussed. Synthetic strategies are clarified as well as their features, advantages, and some representative works. The basic principle and applications of the surface‐limited electrochemical technique such as UPD are highlighted. The comprehensive insights into the mechanistic investigation of energy‐related electrocatalysisat the atomic level are emphasized.